Emulsifying properties and surface behavior of native and denatured whey soy proteins in comparison with other proteins : Creaming stability of oil-in-water emulsions - Palazolo, Gonzalo Gastón (2004)
In this work a comparative study of emulsifying and surface behaviors of native whey soy proteins (NWSP) and denatured whey soy proteins (DWSP) with those of native soy isolates, denatured soy isolates (DSI), and sodium caseinate was done. These samples showed different molecular mass distributions in gel filtration profiles. Dissociation and soluble high-M.W. species in DWSP and DSI were observed. Lower interfacial and surface pressure values were obtained with native samples. Thermal treatment and salt addition enhanced tensioactivity in all fractions. Backscattering measurements of all oil-in-water emulsions, which exhibited a trimodal size distribution of droplets, showed the existence of a negative correlation with the median diameter of droplets. Greater droplet sizes were observed with NaCl addition. The NWSP emulsion had the lowest stability against creaming. Denaturation of this sample increased stability and favored air incorporation in emulsions. Destabilization depends not only on median droplet size but also on floc formation and structure. NaCl addition negatively affected the creaming stability only in emulsions formulated with soy isolates. The use of denaturation to enhance the surface and emulsifying properties of whey soy proteins would allow their use in food emulsions.